Bird Swarm Algorithm Optimized TIDD Controller for Multi-area Load Frequency Control Application - Bhagat, Sanjeev Kumar; Behera, Sadasiva; Saha, Arindita; Bal, Tanima; Chiranjeevi, Tirumalasetty; Devarapalli, Ramesh; Babu, Naladi Ram (SN computer science, 2023)
This article presents the application of bird swarm algorithm optimized tilt-integral double derivative controller for multi-area load frequency control. The proposed system comprises one thermal and realistic dish-Stirling solar thermal system unit in each area. A novel controller named as tilt-integral-double derivative controller has been designed as a supplementary controller. The bird swarm algorithm has been successfully utilized to optimize the controller and other parameters. The comparative analysis of system dynamics responses with proportional-integral-derivative, tilt-integral-derivative, and tilt-integral-double derivative controllers concluded that the system with proposed tilt-integral-double derivative controller outperformed in terms of peak overshoots, undershoots and settling time. The system dynamics performance is also analyzed with proposed tilt-integral-double derivative controller considering various optimization techniques such as crow search, cuckoo search and bird swarm algorithm, and it is observed that the system performance with proposed algorithm provides better dynamics and also converge faster than other optimization techniques. The study of realistic dish-Stirling solar thermal system integration on system dynamics explored improves in system dynamic performances. Moreover, the sensitivity analysis suggested that it is not necessary to change the system loading or other parameters for the wider range.